Who moved my cheese? an amazing way to deal with change in your work and in your life - Johnson, Spencer (New York Putnam, 1998)
ith Who Moved My Cheese? Dr. Spencer Johnson realizes the need for finding the language and tools to deal with change--an issue that makes all of us nervous and uncomfortable.
Keywords: Change (Psychology)